Linguistic Accuracy in Spanish Adolescent Learners’ EFL Writings - García-Pastor, María Dolores (Miscelánea: A Journal of English and American Studies, 2018)
This paper presents an exploratory study of linguistic accuracy in Spanish adolescent students’ writings in English as a foreign language (EFL) (N = 54) by examining learner errors in morphology (grammar), lexis and syntax. The effect of two writing task variables, i.e. length and time constraints, was also considered. Linguistic accuracy in students’ texts was mostly characterised by non-transfer errors in morphology with verbal tense and aspect appearing as the most problematic areas. Transfer errors were also present in students’ texts, but were more frequent in syntax and lexis. Additionally, the percentage of error occurrence in shorter essays was higher than in longer essays, and time constraints did not affect the number of students’ errors. These findings may provide information to Spanish adolescent students of English and their teachers that could be useful to improve the learning and teaching of writing in EFL.
Keywords: EFL; linguistic accuracy; learner errors; foreign language writing; adolescent learners